Teaching Czech at the Bohemian Studies at the University of Vienna - Pochylova, Schurz Marketa (Bohemica Olomucensia, 2023)
In addition to the theoretical study of the language, students of Czech studies in Vienna can also develop their practical knowledge of Czech by communicating with native speak- ers from the Czech minority. Students with different language backgrounds meet in the same class during their studies. We asked ourselves whether previous knowledge of the Slavic language is an advantage or disadvantage. We pointed out the typical manifestations of interference from German to Czech and showed what errors it causes and on which language levels.
Keywords: Bohemistik at the Institute of Slavic Studies in Vienna; Czech minority; interference; mistakes; native /non-native speaker